A Structural Equation Model of Governing Factors Influencing the Development of Sustainable Insurance Product in the Future: Evidence from Indonesian Insurance Industry - Ismalina, Poppy; Junarsin, Eddy; Maftuchah, Istiana (The International Journal of Financial Systems, 2023)
Designing and proposing sustainable insurance programs to insurance companies that run their businesses in Indonesia have been one of the insurers’ approaches to creating more stable and certain industry climate. Moreover, the Indonesian Financial Services Authority or OJK encourages financial services sector actors in creating, developing sustainable product innovations, and supporting financing of production activities that can create economic growth, social justice and environmental quality improvement. We conduct survey and analyze whether insurance companies in Indonesia are interested in implementing sustainable finance in insurance industry and developing sustainable insurance products. Participants’ responses depict insurance firms’ paradigm on sustainable insurance. In this study a framework is proposed for governing factors that impact the development of sustainable insurance product in the future such as the level of knowledge, readiness, and current sustainable insurance product development. To clarify the relationships, a structural equation model is utilized to examine the framework fit with the hypothesis for the four latent variables of this study. Acceptable goodness of fit is established for validity of the measurement model. The test of validity is accepted for the structural model in this study. The SEM results conclude that an insurer’s knowledge of sustainable finance principles affects the insurance firm’s readiness to implement sustainable insurance. Subsequently, the insurer’s readiness affects its current level of sustainable insurance product development. Eventually, the insurer’s knowledge and current development in sustainable insurance products have a positive effect on the insurance firm’s willingness to develop sustainable insurance products in the future. Thus, this study provides valuable information about factors affecting the development of sustainable insurance products in the future as a key for a successful implementation of sustainable finance in Indonesian insurance industry.